Formulasi Kebijakan Pengelolaan Hutan bersama Masyarakat di Taman Nasional Gunung Ciremai - Farma Yuniandra; Cecep Kusmana; Dodik Ridho Nurrochmat (Institut Pertanian Bogor (IPB University), 2007)
Implementation of Collaborative Forest Management (CFM) at 25 villages in the Mount Ciremai, Kuningan Regency, West Java Province has became a problem because of specifying as national park. The objectives of this research were to analyze policy of CFM, examining implementation and it’s impact in Mount Ciremai National Park, and to formulate policy strategy of CFM in Mount Ciremai National Park. Methods of this research were policy analysis, descriptive analysis, AHP, and SWOT. Implementation of the CFM policy in Kuningan Regency consisted of: socialization, forming of CFM Forum, mapping, inventory, planning of village, NKB, NPK, and village regulation. Economic impact from the policy of CFM in Kuningan Regency contributed the income to about 7,71% from the nominal of Rp 3.336.573,- per capita per year and poverty rate after CFM in general was relatively low. This research showed that CFM policy strategies that should be applied in Mount Ciremai National Park were socialization of economic value of the national park, regulation’s intervention, developing the utilization of national park, and empowerment of the community economic.